Upacara Adat Ngasa di Kampung Budaya Jalawastu dalam Perspektif Teologis - Adawiyah, Siti Rubay’atul (Jurnal Riset Agama, 2022)
This article describes the Ngasa traditional ceremony in the Jawastu Cultural Village from a theological perspective. Because it has not been widely reviewed in other studies with the theme of culture in the view of theology. This research method is a qualitative descriptive field research. The purpose of this study is to analyze: 1) The history of the Ngasa traditional ceremony in the Jalawastu Cultural Village; 2) Theological values contained in the Ngasa traditional ceremony; 3) Ngasa traditional ceremony in theological perspective. The results of this study are: First, the Ngasa traditional ceremony existed hundreds of years ago before Islam entered a group of followers of the Sunda Wiwitan teachings. At first the Ngasa traditional ceremony was carried out by hamlets or villages located on the slopes of Mount Kumbang. Second, the existence of theological values contained in the Ngasa Traditional Ceremony, namely: 1) Divine values; 2) Human Values; 3) Social values; 4) Value Rituals; 5) Value of life; 6) Spiritual Values. Third, from a theological perspective, especially the theological, Ngasa traditional ceremonies are not in line with Islamic creed in praying and burning incense and offerings. The conclusion of this study is that the teachings and rules of the ancestors still apply and they are afraid that if they violate these rules, their ancestors are angry, so that a disaster occurs and it is believed now, even though Islam has entered the village of Jalawastu. This proves that Sunda Wiwitan’s belief is still strong and still maintains.Â